Clinical utility of a standardized chronic hypersensitivity pneumonitis exposure questionnaire. Issue 4 (6th November 2022) - Barnes, Hayley; Chambers, Daniel; Grainge, Chris; Corte, Tamera J.; Bastiampillai, Shalini; Frenkel, Simon; Westall, Glen; Collard, Harold; Glaspole, Ian
Abstract: Background and Objective: Identification of an exposure is integral to the diagnosis, management, and prognostication of chronic hypersensitivity pneumonitis (CHP). Standardized questionnaires may aid in the identification of exposures, however, there currently are no evidence‐based patient‐validated questionnaires available. Key qualifiers (including duration and frequency) which indicate exposure relevance are also poorly defined. This study assessed the use of a standardized CHP exposure questionnaire in the identification of exposures and diagnostic confidence of CHP. Methods: People with a multi‐disciplinary meeting (MDM) diagnosis from five Australian interstitial lung disease (ILD) expert centres who provided informed consent were included. Participants completed a previously developed standardized CHP Exposure Questionnaire. Responses were collected with the participant's MDM data, including diagnosis, diagnostic confidence, and clinician‐elicited exposures. Results: One hundred thirty participants (IPF = 58, CHP = 24, CTD‐ILD = 17, unclassifiable = 19, other = 12) were included. In 33% of CHP participants, a standardized questionnaire elicited an exposure where the clinician did not. 63% of these had provisional low confidence CHP; and an exposure history would have increased the diagnostic confidence in these cases. Using the standardized questionnaire, 96% of CHP participants reporting any exposure, compared with 75% of non‐HP ILD participants. CHP participants were 3.5 times more likely ( p  = 0.004) to report their symptoms improved on avoidance, and 2.3 times more likely ( p  = 0.018) to report daily frequent exposure, compared with non‐HP ILDs. Conclusion: A standardized questionnaire which elicits exposure characteristics in addition to presence or absence of relevant exposures can increase the diagnostic confidence of CHP and reduce the proportion of antigen‐indeterminate CHP. Abstract : This case–control study found that a standardized evidence‐based chronic hypersensitivity pneumonitis (CHP) exposure questionnaire increased the diagnostic confidence of CHP and reduced the proportion of antigen‐indeterminate CHP. See related Editorial